Development of E-LKPD Differentiated Learning of Ecosystem Material to Improve Critical Thinking Skills and Learning Outcomes - Rista Wahyu Mahanani; Suhartini (Jurnal Penelitian Pendidikan IPA, 2025)
The aims of this research is to develop  electronic worksheet differentiated instruction on topic of mangrove ecosystem which improve critical thinking skills. The quality of worksheet determined based on validity, effective, and practical criteria. This research is research and development (R n D and using Plomp model. The subjects are 65 students X grade Senior High School of Abu Bakar Kulon Progo. Data analysis technique uses descriptive analysis and MANOVA test. The results from implementing electronic student worksheet obtained a score of media validity is 81.67, the category is very valid, a score of material validity is 87.86 the category is very valid. The score of practicality worksheet is 97 and 80 from teachers and students, both in the very practical category. Worksheet has significant effectiveness as evidenced by a significance of 0.000 < 0.05, which means that there is a significant difference in critical thinking skills between the control and experimental classes after learning with electronic student worksheet differentiated instruction.